Evolutionary insights and functional diversity of gasdermin family proteins and homologs in microorganisms - Wang, Shule; Ma, Tingbo; Xia, Xiaoyi; Zhang, Leiliang (Frontiers in Immunology, 2024)
The gasdermin protein family and its homologs in microorganisms have gained significant attention due to their roles in programmed cell death, immune defense, and microbial infection. This review summarizes the current research status of gasdermin proteins, their structural features, and functional roles in fungi, bacteria, and viruses. The review presents evolutionary parallels between mammalian and microbial defense systems, highlighting the conserved role of gasdermin proteins in regulating cell death processes and immunity. Additionally, the structural and functional characteristics of gasdermin homologs in microorganisms are summarized, shedding light on their potential as targets for therapeutic interventions. Future research directions in this field are also discussed to provide a roadmap for further investigation.